Suggestive and dynamic Discourse in the Holy Qur’an: A study between the Meccan and Madinah Revelations - Kadhim , Waseem Abbas; Al-Mulla, Jabbar Kadhim (Journal of Ecohumanism, 2024)
The research shed light on one of the phenomena of language and its connotations, which is: (suggestion and dynamic) within the utterance. This phenomenon has been shown to have a presence in the Qur’anic text, and the reason for this presence and the basis for that phenomenon is in the Qur’an. Since the latter constitutes the highest rhetorical and declarative value in our hands today from the time of revelation to the present time, it is natural for it to witness a high use of language styles and vocabulary in its texts. The research follows up on the phenomenon of (suggestion and dynamic) within the Qur’anic discourse in general and its transformations between the Meccan and Madinah revelation discourse in particular. The last entry (Meccan and Madinah) is the mainstay of the research and its main tributary. This restriction took the form of a single use of a word with a different inflection and dynamic, which makes the Qur’anic text, in its sensual language, consistent with the situation, the moment, the environment, and the addressee, through which it keeps pace with the described situation and the point that the addressee seeks to convey to the minds of the addressees in particular. The Qur’an deals with the two environments of revelation, each with a specific situation and different understanding. Thus, this discourse led to the presence of a dynamic, suggestive discourse for each stage of the revelation (Mecca and Medina) that reflects the environment that embraces the discourse and its positions. The researcher was required to develop a hypothesis that was consistent with the framework of the study, investigate the occurrences of the phenomenon, analyze the motives and reasons behind it, and study the diversity in this discourse between the two revelations.